Pengetahuan Pendaki Gunung tentang Hipotermia - Meilenia Laras; Mustriwi Mustriwi (Jurnal Kesehatan Hesti Wira Sakti, 2021)
Introduction Knowledge of hypothermia is very important to be known by mountaineers because it can be a provision when encountering colleagues who experience this on the trail. The purpose of this research was to find out an overview of mountaineers knowledge about hypothermia in the Nature Lovers Organization "PRIPALASA" Singosari Sub-District Malang District. Methode This research uses descriptive methods. The population is all members of the Nature Lovers Organization "PRIPALASA" Singosari Sub-District Malang District. The sampling technique with total sampling.The number of samples as many as 30 people. The research variable is the mountaineer's knowledge of hypothermia. The research was conducted on January 28, 2021. The instrument used is a questionnaire. Data analysis uses univariate analysis. Results The results showed most of them had moderate knowledge about hypothermia as many as 14 people (47%), almost half had less knowledge of 10 people (33%), and a small percentage had good knowledge as many as 6 people (20%). Conclusion Some factors that are thought to influence the results of the research are age, education, and experience. It is expected that respondents can increase their knowledge by looking for information about hypothermia from the media, the internet, following counseling, or asking friends so as to reduce the occurrence of hypothermia during climbing.